Peran Brand Image dan Perceived Value terhadap Repurchase Intention dengan Brand Trust sebagai Variabel Intervening pada Pengguna E-Commerce Tokopedia - Haris Nega Aprilian; Olivia FachrunnisaFachrunnisa (ARZUSIN, 2026)
Intense competition in the e-commerce industry in Indonesia requires companies to strengthen the factors that can increase consumers’ repurchase intention. This study aims to analyze the effect of brand image and perceived value on repurchase intention, with brand trust as an intervening variable among Tokopedia users. This study used a quantitative approach with an explanatory research design. Data were collected through a questionnaire administered to 150 Tokopedia user respondents selected using purposive sampling, then analyzed using SmartPLS 4 through outer model and inner model testing. The results showed that brand image, perceived value, and brand trust had a positive and significant effect on repurchase intention. In addition, brand image and perceived value also had a positive effect on brand trust, and brand trust was able to mediate the relationship between these two variables and repurchase intention. These findings confirm that improving brand image and consumers’ perceived value can strengthen brand trust and encourage repurchase intention. The implications of this study indicate the importance of marketing strategies that focus on strengthening brand image, increasing perceived value, and building brand trust to enhance Tokopedia customer loyalty.